2017
DOI: 10.18632/oncotarget.15957
|View full text |Cite
|
Sign up to set email alerts
|

Stellettin B induces apoptosis in human chronic myeloid leukemia cells via targeting PI3K and Stat5

Abstract: Novel agents are still urgently expected for therapy of chronic myeloid leukemia (CML). The in vitro anti-leukemia activity of Stellettin B (Stel B), a triterpenoid we isolated from marine sponge Jaspis stellifera, on human CML K562 and KU812 cells was recently investigated. Stel B inhibited K562 and KU812 cell proliferation with IC50 as 0.035 μM and 0.95 μM respectively. While no obvious cell cycle arrest was observed, apoptosis was induced in K562 cells after Stel B treatment. The Stel B-induced apoptosis mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 36 publications
2
31
0
Order By: Relevance
“…The ability of C828 in inhibiting the phosphorylation of Akt/mTOR and NF-κB pathways is particularly relevant as TNBC has constitutive activation of these pathways [ 10 , 11 , 17 ], which favors metastatic processes and chemo-resistance mechanisms [ 16 , 18 ]. Our result are in agreement with those reported for stellettin B, a triterpene that was derived from marine sponge Jaspis stellifera inhibited proliferation and induced cell death in human non-small cell lung cancer, human chronic myeloid leukemia and human glioblastoma cancer cells by inhibiting Akt/mTOR signaling pathways [ 68 , 69 , 70 ]. Moreover, it is known that the upregulation of Akt and NF-κB signaling pathways is related to the activation of cyclin D1 that leads to proliferation of cancer cells [ 21 , 71 ] and decline in CDKI, p21, thus inhibiting apoptosis [ 72 , 73 , 74 , 75 , 76 , 77 ].…”
Section: Discussionsupporting
confidence: 92%
“…The ability of C828 in inhibiting the phosphorylation of Akt/mTOR and NF-κB pathways is particularly relevant as TNBC has constitutive activation of these pathways [ 10 , 11 , 17 ], which favors metastatic processes and chemo-resistance mechanisms [ 16 , 18 ]. Our result are in agreement with those reported for stellettin B, a triterpene that was derived from marine sponge Jaspis stellifera inhibited proliferation and induced cell death in human non-small cell lung cancer, human chronic myeloid leukemia and human glioblastoma cancer cells by inhibiting Akt/mTOR signaling pathways [ 68 , 69 , 70 ]. Moreover, it is known that the upregulation of Akt and NF-κB signaling pathways is related to the activation of cyclin D1 that leads to proliferation of cancer cells [ 21 , 71 ] and decline in CDKI, p21, thus inhibiting apoptosis [ 72 , 73 , 74 , 75 , 76 , 77 ].…”
Section: Discussionsupporting
confidence: 92%
“…In all four cell lines, Stellettin B induced an increase in the reactive oxygen species (ROS) levels that was linked to apoptosis. In leukemia cells, it triggered the mitochondrial pathway through upregulation of Bak and Bax protein levels, downregulation of Bcl-2, and induction of MOMP [ 46 ]. In SF295 and A549 cell lines, the pathway was not investigated [ 48 ].…”
Section: Proapoptotic and Anti-inflammatory Effectsmentioning
confidence: 99%
“…More recently, Chen et al [ 47 ] and Wang et al [ 48 ] confirmed Stellettin B’s ability to trigger apoptosis via Akt inhibition in A549, K562 and KU812 cells. However, as opposed to the evidence on glioblastoma cells, the authors showed the inhibition of the expression of p110, the catalytic subunit of PI3K, and the phosphorylation of phosphoinositide-dependent kinase-1 (PDK1), another Akt upstream protein [ 46 , 47 ]. An interesting experiment would be to evaluate the PDK1 levels in Stellettin B-treated SF295 cells.…”
Section: Proapoptotic and Anti-inflammatory Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most recent biological research on stellettin B was reported by Kong and co-workers 104 in 2017. They investigated in vitro anti-leukemia activity of stellettin B on human CML K562 and KU812 cells.…”
Section: Bioactivities Of Stellettins a And Bmentioning
confidence: 99%